Improving Student Motivation in Learning Pancasila Education with Bamboozle Media Games in Class VII B SMP Negeri 51 Palembang - Handoko, Sidik; Dianti, Puspa; Linda Hartati, Laili (PPG IKIP Siliwangi, 2025)
The use of learning media has an important role in increasing the enthusiasm and motivation of students. Interesting media can create a learning atmosphere that is more varied and not monotonous. Educational games like Bamboozle can make learning more fun and engaging. This study aims to increase the learning motivation of 31 students in class VII.B through the use of Bamboozle educational games. The method used is Classroom Action Research (PTK), with data collection techniques in the form of observation and documentation. The obtained data were analyzed descriptively and quantitatively. The results showed that the application of Bamboozle educational games was able to increase students' learning motivation. The effect can be seen from the results in cycle I, which showed a motivation level of 53% in the moderate category and experienced a significant increase in cycle II to 75% in the high category. Thus, it can be concluded that the use of Bamboozle educational games is effective in increasing students' learning motivation.